The relationships between personality and Facebook photographs: A study in Taiwan - Cheng-Liang Yang (Cogent Business & Management, 2019)
The current study aimed to investigate the relationships between Facebook users' personality traits and Facebook photos categories relating to the users' daily life events. Five hundred and seventy-five Facebook users participated in this study. The results indicated that Extraversion was the strongest significant predictor for most photo categories. The other four personality traits, i.e. Openness to experience, Conscientiousness, Emotional stability, and Agreeableness, were also related to certain photo categories. The current study's findings expand literature a new field to explore Facebook users' underlying dispositions and extend current knowledge to a deeper understanding of what kinds of photo being predicted by what dispositions, and provides a new approach to assessment of applicants' and employees' personality in addition to self-reported personality tests.
Keywords: 650; personality; human resource management; self-expression; Facebook photos; social networks; room with a cue model (RCM)